CSR dan Nilai Perusahaan: Peran Odd-Even Effect Dewan Direksi, Umur dan Ukuran Perusahaan - Dewi, Ayu Aryista; Ariyanto, Dodik (E-Jurnal Akuntansi; Vol 32 No 12 (2022)DO - 10.24843/EJA.2022.v32.i12.p03, 2022)
Firm value is one indicator in investing. The study aims to examine the effect of Corporate Social Responsibility (CSR) on firm value by using firm age, board of directors odd-even effect and company size as moderating variables for companies listed on the Sri Kehati Index from 2013-2019. The research sample consisted of 84 observations and data were analyzed using multiple linear regression models and Moderated Regression Analysis (MRA). The results of the study show that CSR has a positive and significant effect on firm value. The results also show that firm age, board of directors odd-even effect and firm size moderate the relationship between CSR and firm value. Keywords: Board Meeting Efficiency; Company Value; Corporate Social Responsibility; Company Size; Company Age